PENGARUH INDEPENDENSI, KUALITAS AUDIT DAN MEKANISME CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2008-2012 - Budi Setiawan; Kennedy -; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of independence on the integrity of financial statements, examine the effect of audit quality on the integrity of the financial statements, and examine the effect of corporate governance mechanisms include institutional ownership, managerial ownership, audit committees and independent commissioner for the integrity of the financial statements. The population of this study are all engaged in a manufacturing company that went public in the Indonesia Stock Exchange in 2008 up to 2012 as many as 104 companies. While the sampling method of purposive sampling is conducted sampling considerations in the determination of the sample with certain criteria, in order to obtain a sample of 68 firms. While analysis of the data using linear regression. The study states that the independence, audit quality, audit committee and independent commissioners affect the integrity of the financial statements, while institutional ownership and managerial ownership does not affect the integrity of the financial statements which can be seen from the calculated value of t <t-table. This means that institutional ownership and managerial ownership in manufacturing firms is not among the factors that can affect the integrity of the financial statements.Keywords: Independence, Quality Audit, Audit Committee, Independent Commissioner, Institutional Ownership, Managerial Ownership, Integrity Financial Statements